Transnasal Endoscopic Treatment of Pterygopalatine Fossa and Infratemporal Fossa Malignancies - Tang, Ing Ping; Narayanan, Prepageran (Thieme Medical Publishers, Inc., 2019)
The transnasal endoscopic resection of pterygopalatine fossa andinfratemporal fossa malignancies is an alternative surgical tech-nique to open approaches. With the advancement of endoscopicinstrumentation and better understanding of endoscopic skullbase anatomy, a dramatic milestone has been achieved in trans-nasal endoscopic skull base surgery. This approach not onlyprovides better visualization and manipulation of tissues in ananatomically complex area, but also dramatically reduces the sur-gical complication and morbidity rates. Reports also showed thatpiecemeal or layered resection of sinonasal malignancies intransnasal endoscopic surgery did not compromise the oncologicresection. This method maximizes the chances of complete resec-tion and good postoperative surveillance.